1973
DOI: 10.1111/j.1699-0463.1973.tb00210.x
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON STACHYBOTRYS ALTERNANS I. ISOLATION OF TOXICOGENIC STRAINS FROM FINNISH GRAINS AND FEEDS

Abstract: Nineteen Stachybotrys alternans strains isolated from animal feeds, fodder or bedding and from grain for human consumption were tested for their toxin‐producing capacity on a mixture of wheat, oats and barley. Ultraviolet light was applied during isolation of the fungi. Nine out of the 19 strains were toxic to white mice in a feeding experiment of two week's duration. Five selected strains were also tested by the rabbit skin test and by the feeding test with guinea pigs. Clinical symptoms and patho‐anatomical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In an earlier study (Korpinen 1973) 9 out of 19 strains tested were found by a feeding test with mice to be toxic. The material was included in the present tissue culture toxicity tests.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In an earlier study (Korpinen 1973) 9 out of 19 strains tested were found by a feeding test with mice to be toxic. The material was included in the present tissue culture toxicity tests.…”
Section: Discussionmentioning
confidence: 95%
“…By using ultraviolet light rhe abundant overgrowth of many fungus species may also be prevented, thus providing room for Stachybotrys growth. The latter method was used in an earlier work (Korpinen 1973). I n the present work tht: filter paper method was chosen mainly for practical reasons.…”
Section: Discussionmentioning
confidence: 99%